Phytochemical Screening and Mineral Composition of the Leaves of Ocimum gratissimum (Scent Leaf) - Alexander, Priscilla (International Journal of Applied Sciences and Biotechnology, 2016)
The leaves of Ocimum gratissimum having some ethno-medicinal applications were investigated. The phytochemicals screening of the leaves using Standard Methods and further analysis with HPLC revealed the presence of tannins, saponins, flavonoids, alkaloids, phlobatanins, terpenoids, steroids and cardiac glycosides. The elemental analysis was carried out using Atomic Absorption Spectrophotometer (AAS). The result revealed the presence of Na (0.311±0.049), Ca (0.138 ±0.111), Mg (1.712 ± 0.537), K (0.261± 0.077), Mn (0.457±0.107, Pb (0.005 ± 0.002), Zn (0.200 ±0.06), Cu (0.803±0.818), N (0.286± 0.052), and Fe (0.312 ± 0.067). Cd and Cr were not detected in the samples. This investigation suggested that Ocimum gratissimum leaves are rich in phytochemical constituents which contributed to its medicinal uses. The leaves of Ocimum gratissimum can be said to contain some components of medical value since the chemical components elaborated by it are active principles (alkaloid, steroids and glycosides). Ocimum gratissimum also contain most of the essentials elements indicating its nutritive values and less toxic as Cd and Cr were not detected in the leaf. Int J Appl Sci Biotechnol, Vol 4(2): 161-165